PENGARUH HUTANG JANGKA PENDEK DAN HUTANG JANGKA PANJANG TERHADAP LABA BERSIH SUB SEKTOR INDUSTRI OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI PERIODE 2017-2021 - Tetty Widiyastuti (Nusantara Hasana Berdikari, 2022)
Total debt is an important component of every company in running a business to earn a profit. So that the company in processing total debt must be effective and efficient in order to get the maximum net profit return and avoid losses. This study aims to determine the effect of short-term debt and long-term debt on net income of the automotive and component industry sub-sectors listed on the Indonesia Stock Exchange. This study uses a quantitative descriptive method, used to examine a particular population or sample. The independent variable in this study is short-term debt and long-term debt, while the dependent variable is net income. The population in this study are all automotive and component sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. A sample of 20 consists of 5 companies multiplied by 4 years of research. The sample selection is a purposive sampling technique. The analytical technique used is to use multiple linear regression analysis. The results of this study indicate that total debt has a significant effect on the net profit of the automotive and component industries listed on the IDX. From the variables of short-term debt and long-term debt that get the lowest average value of long-term debt, this requires the company to evaluate the use of long-term debt. Meanwhile, when viewed from regression testing, classical assumptions and hypotheses, that each variable is interrelated and has a significant influence.